2012
DOI: 10.1089/bfm.2011.0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mothers' Knowledge, Attitudes, and Practice Towards the Ten Steps to Successful Breastfeeding in Egypt

Abstract: To increase the impact of BFHI on community breastfeeding practices, BFHI should focus on involving the family members with the mother throughout the implementation of the Ten Steps while encouraging maternal support groups and taking cultural differences into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…The majority of included studies were cross‐sectional in nature ( n = 13) (Ogbonna & Daboer ; Petrie et al ; Uchendu et al ; Marais et al ; Ukegbu & Ukegbu ; Oche et al ; Abul‐Fadl et al ; Alade et al ; Ukegbu & Anyikaelekeh ; Adeyemi & Oyewole ; Danso ; Desai et al ; Onah et al ) with the remainder of studies either qualitative ( n = 7) (Murray et al ; Otoo et al ; Nankunda et al ; Ostergaard & Bula ; Ukegbu et al ; Nor et al ; Nduna et al ) or a Randomised Control Trial (RCT) ( n = 1) (Aksu et al ) (Table ). Publication dates ranged from 2007 (Ogbonna & Daboer ) to 2015 (Nduna et al ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of included studies were cross‐sectional in nature ( n = 13) (Ogbonna & Daboer ; Petrie et al ; Uchendu et al ; Marais et al ; Ukegbu & Ukegbu ; Oche et al ; Abul‐Fadl et al ; Alade et al ; Ukegbu & Anyikaelekeh ; Adeyemi & Oyewole ; Danso ; Desai et al ; Onah et al ) with the remainder of studies either qualitative ( n = 7) (Murray et al ; Otoo et al ; Nankunda et al ; Ostergaard & Bula ; Ukegbu et al ; Nor et al ; Nduna et al ) or a Randomised Control Trial (RCT) ( n = 1) (Aksu et al ) (Table ). Publication dates ranged from 2007 (Ogbonna & Daboer ) to 2015 (Nduna et al ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included mothers who had infants between zero and 24 months old ( n = 12) (Ogbonna & Daboer ; Murray et al ; Petrie et al ; Otoo et al ; Uchendu et al ; Marais et al ; Ostergaard & Bula ; Abul‐Fadl et al ; Alade et al ; Danso ; Desai et al ; Onah et al ), and the age of infants was not mentioned in nine studies (Nankunda et al ; Ukegbu & Ukegbu ; Aksu et al ; Oche et al ; Ukegbu et al ; Nor et al ; Ukegbu & Anyikaelekeh ; Adeyemi & Oyewole ; Nduna et al ). Two studies (Ostergaard & Bula ; Aksu et al ) included mothers who intended to breastfeed, five (Marais et al ; Ukegbu & Ukegbu ; Oche et al ; Abul‐Fadl et al ; Alade et al ) who were currently breastfeeding and two (Nankunda et al ; Danso ) with personal breastfeeding experience. Twelve studies (Ogbonna & Daboer ; Murray et al ; Petrie et al ; Otoo et al ; Uchendu et al ; Ukegbu et al ; Nor et al ; Ukegbu & Anyikaelekeh ; Adeyemi & Oyewole ; Desai et al ; Onah et al ; Nduna et al ) did not mention current breastfeeding status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These traditional beliefs have stemmed as far back as ancient times and continue to perpetuate the importance of breastfeeding as the most prevalent method of infant nutrition in Egypt (Ragheb & Smith, 1979). Previous studies that assessed maternal knowledge, attitudes, practices, and beliefs have revealed that the majority of custom-based beliefs are harmless and promote a healthy mother-infant interaction (Abul-Fadl, Shawky, El-Taweel, Cadwell, & Turner-Maffei, 2012;Ahmed, 2008;Harrison, Zaghloul, Galal, & Gabr, 1993;Ragheb & Smith, 1979).…”
mentioning
confidence: 99%